Deregulating fixed voice services? Empirical evidence from the European Union - Mirjam R. J. Lange; Amela Šaric (International Telecommunications Society (ITS), 2014)
This paper analyzes the relationship between the traditional fixed-line, mobile and Voice over IP (VoIP) telephony in the EU. In doing so, it aims at filling the gap in the empirical literature on the substitution patterns between these technologies in a comprehensive way. It relies on demand estimation for fixed-line telephony using a unique data set comprising 25 EU member states for the 2006:Q2 - 2011:Q4 period. Employing instrumental variable approach, demand-side substitution for VoIP as well as mobile telephony services is found to be prevalent. Estimated short-run own- and cross-price elasticities are in the inelastic range, however, in the long run demand is clearly elastic. Hence, our results underpin the Europeans Commission's current decision to lift the ex ante regulation on the fixed-line telephony market.
Keywords: C23; L43; L51; L96; 330; Fixed networks; Mobile services; Market definition; (De)regulation